2010
DOI: 10.3390/s101110339
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of 3D Micro- and Nanoelectrodes for Neuron Recordings

Abstract: In this paper we discuss the fabrication and characterization of three dimensional (3D) micro- and nanoelectrodes with the goal of using them for extra- and intracellular studies. Two different types of electrodes will be described: high aspect ratio microelectrodes for studying the communication between cells and ultimately for brain slice recordings and small nanoelectrodes for highly localized measurements and ultimately for intracellular studies. Electrical and electrochemical characterization of these ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The fabrication process for the small electrodes is similar to that presented in [14] but with two essential changes. First, by utilising a high resistivity wafer (10,000 X cm instead of the previously used 1-20 X cm) we avoid having to isolate the resulting pillars by a thick oxide layer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fabrication process for the small electrodes is similar to that presented in [14] but with two essential changes. First, by utilising a high resistivity wafer (10,000 X cm instead of the previously used 1-20 X cm) we avoid having to isolate the resulting pillars by a thick oxide layer.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously presented a fabrication process for 3D micro-and nanoelectrodes [14]. In the case of the small electrodes, the KOH wet etch based process resulted in very sharp structures, however, after isolation (by silicon oxide deposition) and metal deposition, the tip size was extended to dimensions around 500 nm-1 lm, which is too big for cell penetration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also suggested the use of sharp protruding electrodes (sharp micromachined tips, Si nanowires) to penetrate the membrane of cultured cells, thus directly recording the intracellular potential modulation [3,4]. Nevertheless, penetration into cytoplasm may result harmful for the cell itself, causing alteration in electrical behavior or its death.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional structuring of metallic electrodes has been proposed as a strategy to improve in vitro recording from brain slices [2,3]. Several studies have also suggested the use of sharp protruding electrodes (sharp micromachined tips, Si nanowires) to penetrate the membrane of cultured cells, thus directly recording the intracellular potential modulation [3,4].…”
Section: Introductionmentioning
confidence: 99%